Indeterminasi Sekuensial Pembungaan dan Ketidakmampuan Produksi Kedelai di Lapang Akibat Penambahan Cahaya Kontinu pada Kondisi Terbuka dan Ternaungi - Herdhata Agusta; Imam Santoso (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2005)
Additional continuous light (photoperiod of 24 hours/day) with irradiation value of 0.61 cal/cm2/minute and illumination value of 59 lux was able to suppress the development of flowering, pod building, grain filling and the production of soybean variety Bromo,  so that the sum of flowers, pods and grain production dropped and reached to null value.   However, the plant height increased with remarkable measurement from normally 78.0 cm to be 193.2 cm.  At the later condition the plant lodged and crept.  Due to additional continuous light irradiation at value of 0.03 cal/cm2/minute with average illumination value of 17 lux, the grain production was still null ton/ha.  However, the formed flowers and pods were not well developed.  At very little additional continuous light irradiation at the value of 0.01 cal/cm2/minute with illumination value of  2 lux, soybean production reached only 0.72 tons/ha, which at the normal condition it was able to produce grain legumes in amount to 1.53 tons/ha.  Light shading at the level of 56% could not improve the negative effect of the additional continuous light excess, so that the grain production was not much better.  However, grain production was either not reduced significantly due to the light shading.  It showed that the soybean is well tolerant against the shading treatment at this additional light condition.   Key words :  light, shading, soybean, air carbon dioxide, photoperiod